Long-Term Renal Transplant Outcome in Patients With Posterior Urethral Valves. Prognostic Factors Related to Bladder Dysfunction Management - Amesty, María Virginia; García-Vaz, Claudia; Espinosa, Laura; Martínez-Urrutia, María José; López-Pereira, Pedro (Frontiers in Pediatrics, 2021)
Introduction To obtain a successful renal transplant (RT) outcome in patients with posterior urethral valves (PUV) it is necessary to accomplish an adequate bladder dysfunction treatment. Our aim is to determine prognostic factors related to bladder dysfunction management in long-term RT outcome in patients with PUV. Methods A retrospective review of patients with PUV who received a first RT since 1985 in our institution with at least 5 years of follow-up was performed. Variables analyzed included prenatal diagnosis, age of diagnosis, initial presentation and management, bladder dysfunction treatment, other surgical treatments, pre-transplant dialysis, age of transplantation, type of donor, immunosuppression regimen, vascular and urological complications, rejections episodes, and graft survival. Results Fifty-one patients were included in the analysis. Prenatal diagnosis was done in 37.3%. Median age of diagnosis was 0.30 (0-88) months. Initial presentation was vesicoureteral reflux (VUR) in 78% and obstructive ureterohydronefrosis in 35.3%. Initial management was valve ablation (29.4%), pyelo-ureterostomy (64.7%) and vesicostomy (5.9%). In 33.3% some bladder dysfunction treatment was performed: 21.6% bladder augmentation (BA), 15.7% Mitrofanoff procedure, 17.6% anticholinergic drugs; and 27.5% clean intermittent catheterization (CIC). Pre-transplant dialysis was received in 66.7%. Transplantation was performed at 6.28+/-5.12 years, being 62.7% cadaveric and 37.3% living-donor grafts. Acute rejection episodes were found in 23.6%. Urological complications included recurrent urinary tract infections (UTIs)(31.4%); native kidneys VUR(31.4%); graft VUR (45.1%) and ureteral obstruction (2%). Vascular complications occurred in 3.9%. Mean graft survival was 11.1 +/- 6.9 years. Analyzing prognostic factor that influenced graft survival, patients with CIC or with a Mitrofanoff had a significant better long-term graft survival at 10 years of follow-up (p<0.05), despite of the existence of more recurrent UTIs in them. A better graft survival was also found in living-donor transplants (p<0.05). No significant differences were observed in long-term graft survival regarding native kidneys or graft VUR, BA, immunosuppression regimen or post-transplant UTIs. Conclusion Optimal bladder dysfunction treatment, including CIC with or without a Mitrofanoff procedure, may result in a better long-term graft survival in patients with PUV. These procedures are not related to a worse RT outcome in spite of being associated to more frequent UTIs.